Social-media-enabled learning in emergency medicine: a case study of the growth, engagement and impact of a free open access medical education blog. Issue 1108 (20th October 2017) - Carley, Simon; Beardsell, Iain; May, Natalie; Crowe, Liz; Baombe, Janos; Grayson, Alan; Carden, Richard; Liebig, Ashley; Gray, Chris; Fisher, Ross; Horner, Daniel; Howard, Laura; et al.
Abstract: Background: Clinicians are increasingly using social media for professional development and education. In 2012, we developed the St.Emlyn's blog, an open access resource dedicated to providing free education in the field of emergency medicine. Objective: To describe the development and growth of this international emergency medicine blog. Method: We present a narrative description of the development of St.Emlyn's blog. Data on scope, impact and engagement were extracted from WordPress, Twitter and Google Analytics. Results: The St.Emlyn's blog demonstrates a sustained growth in size and user engagement. Since inception in 2012, the site has been viewed over 1.25 million times with a linear year-on-year growth. We have published over 500 blog posts, each of which attracts a mean of 2466 views (range 382–69 671). The site has been viewed in nearly every country in the world, although the majority (>75%) of visitors come from the USA, UK and Australia. Summary: This case study of an emergency medicine blog quantifies the reach and engagement of social-media-enabled learning in emergency medicine.